Evaluation of the stability of propolis granule and toxicity study in wistar rats - Supakit Khacha-Ananda (2018)
© 2018, Chiang Mai University. All rights reserved. Nowadays, incorporation of natural products into conventional medicine has become a promising approach to improve the health benefits of conventional medicine. Propolis is composed of several chemical constituents which have various pharmacological activities and which are widely used in apitherapy. However, evidence regarding toxicity of propolis products is required. Therefore, stability of propolis granule, as well as its acute and subchronic toxicity on Wistar rats, was investigated. The propolis granule was produced from propolis extract sourced from the Nan province, Thailand. The stability of propolis granule was determined from the total phenolic content and the total flavonoid content of propolis granule. The total phenolic content and the total flavonoid content of propolis granule which was kept at 4°C and the propolis granule which was kept at room temperature were not significantly different throughout 1 year. With regard to acute toxicity, we found that the behavior and physiological changes of the Wistar rats were normal after giving them propolis granule. After propolis granule was orally given to the rats for 60 days, there was no obvious sign of the propolis granule inducing any toxicity throughout the period of experiment. Significant increase in the mean corpuscular volume and decrease in the blood urea nitrogen, creatinine, and aspartate aminotransferase were observed in the rats. Likewise, histopathology examinations of the liver and the kidney did not reveal any morphological alteration. In light of these findings, we concluded that propolis granule does not induce any acute or subchronic toxicity in rats. This information can be further applied with regard to preparation of supplementary diet from the propolis extract for consumption.